Endometrial Adenocarcinoma and Mucocele of the Appendix: An Unusual Coexistence. (16th May 2013) - Kalogiannidis, Ioannis; Mavrona, Amalia; Grammenou, Sophia; Zacharioudakis, Georgios; Aggelidou, Stamatia; Rousso, David
Abstract : Appendiceal mucocele is a rare clinical entity, which is however quite often associated with mucinous ovarian tumor. The coexistence of mucinous cystadenoma of the appendix and endometrial adenocarcinoma has not been reported before. A 49-year-old woman presented to our clinic with postmenopausal bleeding and no other symptom. Endometrial biopsy revealed endometrial adenocarcinoma of endometrioid type (grade I). Preoperative CT scanning revealed an appendiceal mucocele, and a colonoscopy confirmed the diagnosis. The patient underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy and appendectomy. The final histopathological examination showed a mucinous cystadenoma of the appendix and confirmed the diagnosis of endometrioid endometrial adenocarcinoma. The coexistence of appendiceal mucocele and female genital tract pathology is rare. However, gynecologists should keep a high level of suspicion for such possible coexistence. Both the diagnostic approach and the therapeutic management should be multidisciplinary, most importantly with the involvement of general surgeons.